2008
DOI: 10.1139/s07-038
|View full text |Cite
|
Sign up to set email alerts
|

Process water treatment in Canada’s oil sands industry: I. Target pollutants and treatment objectives

Abstract: Process water treatment has become a critical issue for Canada's oil sands industry. Continuous recycling of tailings pond water (TPW) has contributed to a decline in water quality that has consequences for bitumen recovery, water consumption, and reclamation efforts. Potential roles for water treatment were assessed through a review of process water quality and toxicity data from two long-term oil sands operations. Target pollutants were identified according to exceedances of environmental and industrial wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
309
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 500 publications
(313 citation statements)
references
References 42 publications
(80 reference statements)
3
309
1
Order By: Relevance
“…In addition to watershed disturbance, the process of upgrading bitumen to synthetic crude oil involves coking, coke combustion, and production of wastes and fly ash that contain PPE (15)(16)(17). Environment Canada's National Pollutant Release Inventory shows that upgrading is a substantial and increasing source of PPE to air.…”
mentioning
confidence: 99%
“…In addition to watershed disturbance, the process of upgrading bitumen to synthetic crude oil involves coking, coke combustion, and production of wastes and fly ash that contain PPE (15)(16)(17). Environment Canada's National Pollutant Release Inventory shows that upgrading is a substantial and increasing source of PPE to air.…”
mentioning
confidence: 99%
“…While studying the effect of inorganic anions on vanadium leaching from PC in water which contained sulfur, chloride, and bicarbonate ions, Puttaswamy and Liber (2012) showed that bicarbonate ions increased the release of vanadium from PC. Since the concentration of bicarbonate ions in OSPW is very high (775-950 mg/L) (Allen 2008a), this may also promote leaching of vanadium from PC upon its contact with OSPW. In addition, the organic fraction of OSPW contains large variety of compounds which could stabilize vanadium in the aqueous phase and increase its equilibrium concentration as compared to Milli-Q water.…”
Section: Vanadium Leachingmentioning
confidence: 99%
“…As a result, it becomes corrosive and highly toxic due to high concentrations of salts and refractory organic compounds such as naphthenic acids (NAs) . The storage of OSPW has raised several environmental concerns, including the presence of trace concentrations of NAs in surface waters around the oil sands operation facilities due to their leaching from tailings ponds (Allen 2008a).…”
Section: Introductionmentioning
confidence: 99%
“…This OSPW contains several inorganic and organic constituents, some of which have been shown to be acutely toxic to aquatic life. Some of these constituents include high levels of salinity, sulphate, ammonia, conductivity, and naphthenic acids [6]. There is the potential for some of these components to make their way into the Athabasca River through seepage and air deposition [7].…”
Section: Introductionmentioning
confidence: 99%